2014
DOI: 10.1016/j.jss.2014.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding EGF-like growth factor (HB-EGF) promotes cell migration and adhesion via focal adhesion kinase

Abstract: Background Cell migration and adhesion are essential in intestinal epithelial wound healing and recovery from injury. Focal adhesion kinase (FAK) plays an important role in cell-extra cellular matrix (ECM) signal transduction. We have previously shown that heparin-binding epidermal growth factor-like growth factor (HB-EGF) promotes intestinal epithelial cell (IEC) migration and adhesion in vitro. The current study was designed to determine whether FAK is involved in HB-EGF-induced IEC migration and adhesion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…In rodent models, exogenous galectin-3 accelerated re-epithelialization after alkali burn and mechanical abrasion (Cao et al, 2002; Yabuta et al, 2014). Similar examples include experiments showing that β-glucan, ROCK inhibitor, and heparin-binding EGF-like growth factor promote cell adhesion and wound healing in corneal epithelial cells, corneal endothelial cells, and intestinal epithelial cells, respectively (Choi and Joo, 2013; Pipparelli et al, 2013; Su and Besner, 2014). This indicates that ECMs are essential for cell migration in corneal wound healing.…”
Section: Discussionmentioning
confidence: 95%
“…In rodent models, exogenous galectin-3 accelerated re-epithelialization after alkali burn and mechanical abrasion (Cao et al, 2002; Yabuta et al, 2014). Similar examples include experiments showing that β-glucan, ROCK inhibitor, and heparin-binding EGF-like growth factor promote cell adhesion and wound healing in corneal epithelial cells, corneal endothelial cells, and intestinal epithelial cells, respectively (Choi and Joo, 2013; Pipparelli et al, 2013; Su and Besner, 2014). This indicates that ECMs are essential for cell migration in corneal wound healing.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, we also found that CSF-2 significantly enhances the therapeutic capability of stem cells by promoting multi-lineage differentiation (Figure 2A) and migratory capability ( Figures 2D and 2E) in vitro. In addition, CSF-2-treated stem cells actively secreted many known growth factors for promoting tissue regeneration, specifically, AR, 40 G-CSF, 41 GDNF, 42 GM-CSF, 9 HB-EGF, 43 and PDGF 44 ( Figure 6). These results suggest that the CSF-2-mediated beneficial effects of stem cells on tissue regeneration were due, at least in part, to the various secretory factors that regulate diverse biological functions, including cell growth, wound healing, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Scrape wounding was performed as previously described [36], [37]. IEC-6 cells were seeded to each well of a 12 well plate at 80% confluence and incubated in DMEM/F12/Glutamax-I™ (Gibco Invitrogen, Carlsbad, CA) supplemented with 10% FBS at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%